α1-giardin based live heterologous vaccine protects against Giardia lamblia infection in a murine model - Jenikova, Gabriela; Hruz, Petr; Andersson, Mattias K.; Tejman-Yarden, Noa; Ferreira, Patricia C.D.; Andersen, Yolanda S.; Davids, Barbara J.; Gillin, Frances D.; Svärd, Staffan G.; Curtiss, Roy; Eckmann, Lars (Vaccine, 2011)
► Giardia lamblia is a leading protozoan cause of diarrheal disease worldwide. ► Preventive medical strategies are not available against giardiasis. ► Immunization of mice with a live α1-giardin vaccine protected against infection. ► α1-giardin is highly conserved between divergent Giardia isolates. Giardia lamblia is a leading protozoan cause of diarrheal disease worldwide, yet preventive medical strategies are not available. A crude veterinary vaccine has been licensed for cats and dogs, but no defined human vaccine is available. We tested the vaccine potential of three conserved antigens previously identified in human and murine giardiasis, α1-giardin, α-enolase, and ornithine carbamoyl transferase, in a murine model of G. lamblia infection. Live recombinant attenuated Salmonella enterica Serovar Typhimurium vaccine strains were constructed that stably expressed each antigen, maintained colonization capacity, and sustained total attenuation in the host. Oral administration of the vaccine strains induced antigen-specific serum IgG, particularly IgG2A, and mucosal IgA for α1-giardin and α-enolase, but not for ornithine carbamoyl transferase. Immunization with the α1-giardin vaccine induced significant protection against subsequent G. lamblia challenge, which was further enhanced by boosting with cholera toxin or sublingual α1-giardin administration. The α-enolase vaccine afforded no protection. Analysis of α1-giardin from divergent assemblage A and B isolates of G. lamblia revealed >97% amino acid sequence conservation and immunological cross-reactivity, further supporting the potential utility of this antigen in vaccine development. Together. These results indicate that α1-giardin is a suitable candidate antigen for a vaccine against giardiasis.